Reductive transformations of dichloroacetamide safeners: effects of agrochemical co-formulants and iron oxide + manganese oxide binary-mineral systems. Issue 10 (22nd September 2020) - Ricko, Allison N.; Psoras, Andrew W.; Sivey, John D.
Abstract : Abiotic redox transformation rates of dichloroacetamide safeners slow when birnessite is added to slurries of Fe(ii )-amended hematite. Abstract : The toxic effects of herbicides are often incompletely selective and can harm crops. Safeners are "inert" ingredients commonly added to herbicide formulations to protect crops from herbicide-induced injury. Dichloroacetamide safeners have been previously shown to undergo reductive dechlorination in anaerobic abiotic systems containing an iron (hydr)oxide mineral (goethite or hematite) amended with Fe(ii ). Manganese oxides ( e.g., birnessite) are important redox-active species that frequently co-occur with iron (hydr)oxides, yet studies examining the effects of more than one mineral on transformations of environmental contaminants are rare. Herein, we investigate the reactivity of dichloroacetamide safeners benoxacor, furilazole, and dichlormid in binary-mineral, anaerobic systems containing Fe(ii )-amended hematite and birnessite. As the molar ratio of Fe(ii )-to-Mn(iv ) oxide increased, the transformation rate of benoxacor and furilazole increased. The safener dichlormid did not transform appreciably over the sampling period (6 hours). The concentration of pH buffer ([MOPS] = 10–50 mM), ionic strength ([NaCl] = 10–200 mM), and order of solute addition ( e.g., safener followed by Fe(ii ) or vice versa ) do not appreciably affect transformation rates of the examined dichloroacetamide safeners in Fe(ii ) + hematite slurries. The presence of agrochemical co-formulants, including the herbicide S -metolachlor and three surfactants, in solutions containing Cr(H2 O)6 2+ (as a model homogeneous reductant) also did not substantially influence rates of safener transformation. This study is among the first to examine laboratory systems of intermediate complexity ( e.g., systems containing mixtures of agrochemical co-formulants or mineral phases) when assessing the environmental fate of emerging contaminants such as dichloroacetamide safeners.